Determinants of coronary heart disease among adults: a case-control study - Sudikno Sudikno; Srilaning Driyah; Julianty Pradono (Universa Medicina, 2023)
BackgroundAccording to recent World Health Organization data, coronary heart disease (CHD) remains the leading cause of death worldwide. Although the risk factors of this disease are well known, the strength of these factors varies in different populations. The aim of the study was to assess the determinants of CHD in Indonesian adults aged 25 years and over. MethodsA case–control study was carried out involving 592 subjects aged 25 years and over (444 controls and 148 cases). Participants were interviewed using validated questionnaires. Physical examinations and supporting examinations were conducted. The Chi square test, Fisher’s exact test, and independent t test were used to analyze the data. To determine independent predictors of CHD, the odds ratio (OR) was determined via the multiple logistic regressions test. ResultsThe CHD subjects (case group) showed higher blood sugar and systolic pressure than non-CHD subjects (controls), with mean fasting blood sugar of 92.53±27.05 mg/dL vs 88.29 ±23.43 mg/dL (p=0.038), 2-hour postprandial blood sugar of 133.15±65.09 mg/dL vs 120.87±44.60 mg/dL (p=0.000), and systolic blood pressure of 89±27.62 mmHg vs 129.98±10.58 mmHg (p=0.002). The logistic regression analysis in the case group showed that higher education (college) had a 2.32-fold greater effect (95% CI. 1.01-5.35) on CHD incidence compared to the control group. ConclusionsThis study has demonstrated that the most frequent risk factor for CVD in adults aged 25 years and over is higher education. Control and prevention of CHD need to be done with regular control of blood sugar levels and blood pressure to stabilize them within normal limits.